Finite Element Analysis on Reinforced Concrete Beams Strengthened with GFRP (Glass Fiber Reinforced Polymer) Using Software - Surahman, Ridho; Isneini, Mohd.; Alami, Fikri (Universitas Lampung, 2020)
In testing reinforced concrete beams strengthened with 4 layers of GFRP can increase the maximum load up to 112% (Nalarita, 2019). The test can be done by modeling using finite element based software.The beam that is modeled has a dimension of 1,7 m long, 15 cm wide and 15 cm high with 4 layers of 1,3 mm/layer GFRP. The beams that are modeled are only a quarter section because of symmetrical geometry and loading.The percentage difference between the results of modeling and experimental tests on normal beams is 1,49% for deflection in the middle span. The crack that occurs in normal beams in modeling and experimental shows the same crack pattern, which is flexural crack. The percentage difference between modeling and experimental tests on the strengthened beam is 21,81% for the deflection in the middle span. In experimental and modeling tests, the applied GFRP undergoes debonding before the concrete compressive strain reaches its ultimate strain.Keywords: Concrete, GFRP, debonding, modeling